Modification of Ring Blade on Pineapple Peeler - Swastika Nusantari; Achwil Putra Munir; Lukman Adlin Harahap (Universitas Sumatera Utara, 2015)
Pineapple is a unique tropical fruit. Beside it has sharp scales on its skin, it also has a juicy texture and it has sharp eyes through the outer flesh. This research was held to modify and to expand the pineapple peeler in order to simplified pineapple peeling with ring blade so we could peel a pineapple better and to compare the result to the previous blade. As the name, this blade has shaped like a ring and the cutting side was honed and was sharpened. The capacity of pineapple peeler using ring blade was 39,05 kg/hour. The criteria of peeled pinapple could be seen that there was no pineapple eyes on the outer flesh of the fruit. Losses fruit percentage using ring blade was 33,30%. Keywords : modification, pineapple peeler. : ring blade